PENGARUH MOTIVASI PELAYANAN PUBLIK DAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP KINERJA ORGANISASI SEKTOR PUBLIK DI KOTA TANGERANG - Andi Kusuma Negara; Hendra Galuh Febrianto; Amalia Indah Fitriana (Prosiding Simposium Nasional Multidisiplin (SinaMu), 2019)
Efforts by the Tangerang City Government to improve accountability and approval of the administration of government were quite successful. This study analyzes the motivational factors of public service and perceived organizational support that support the improvement of the performance of community organizations in the city of Tangerang. The tendency of motivation for public services and organizational support that is felt can support organizational performance improvement. In order to analyze these factors, a research model was developed which was developed from the literature review. This model has two hypotheses with three variables: public service motivation, perceived organizational support and organizational performance. Data analysis of 115 people who have been permanent employees of the government in Tangerang City was conducted using Structural Equation Modeling (SEM) as an analytical tool using the LISREL 8.8 program. The results of this study are the motivation of public services that are significant for the performance of public sector organizations in the city of Tangerang. Perception of Organizational Support has a significant effect on the performance of public sector organizations in Tangerang City.Keywords: Public Service Motivation, Perceived Organizational Support and Organizational Performance